Delvis människa, delvis organisation (Sociologisk Forskning, 1993)
Partly human, partly organizationIn this article the phenomenon of organization is discussed and its consequences for the understanding of human actions and human choices are examined. Affiliation to organizations are found to be both restrictions on and preconditions for most human action. In this connection families are regarded as organizations as well as enterprises, voluntary associations and states. Human action is primarily action on behalf of organizations where individuals are partly human, partly organization. To understand the meaning of action on behalf of organization it is important to realize that people rarely choose their organizational affiliation. People are selected. This means that actions on behalf of organizations cannot be regarded as expressions of individual choices. Actions on behalf of organizations are generally characterized by a dual involvement.